THE EFFECT OF DIABETES SELF-MANAGEMENT EDUCATION ON LIFESTYLE PATTERNS AMONG ELDERLY PATIENTS WITH DIABETES MELLITUS - Nurjannah; Desy Marta (Jurnal Cakrawala Keperawatan, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic disease that significantly affects the elderly, often leading to complications and reduced quality of life. Lifestyle management plays a crucial role in controlling DM, and palliative care education can enhance self-care and well-being among elderly patients. Purpose: This study aimed to examine the effect of palliative care teaching methods on the lifestyle patterns of elderly patients with diabetes mellitus at Lima Ilir Community Health Center in 2025. Methods: A quantitative quasi-experimental study with a one-group pretest-posttest design was conducted. Thirty-one elderly patients with DM were selected using purposive sampling. The intervention involved palliative care teaching using brochures as educational media. Lifestyle patterns were measured before and after the intervention using the Health-Promoting Lifestyle Profile II (HPLP II) questionnaire. Data were analyzed using paired sample t-test with SPSS. Results: The results showed a significant improvement in lifestyle patterns after the intervention. Before the intervention, 54.8% of participants had poor lifestyle habits, while 22.6% and 22.6% were categorized as moderate and good, respectively. After the intervention, no participants remained in the poor category; 25.8% were moderate, 54.8% good, and 19.4% very good. Statistical analysis revealed a significant difference in lifestyle scores before and after the intervention (p = 0.000, p < 0.05). Conclusion: The palliative care teaching method effectively improves lifestyle patterns among elderly patients with diabetes mellitus. Providing structured education and guidance enhances patients’ understanding of self-management, including diet, physical activity, stress management, and adherence to medication, thereby promoting better quality of life.